2014
DOI: 10.1007/s13361-014-0953-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Mechanism of the “Proline Effect” in Tandem Mass Spectrometry Experiments: The “Pipecolic Acid Effect”

Abstract: The fragmentation behavior of a set of model peptides containing proline, its four-membered ring analog azetidine-2-carboxylic acid (Aze), its six-membered ring analog pipecolic acid (Pip), an acyclic secondary amine residue N-methyl-alanine (NMeA), and the D stereoisomers of Pro and Pip has been determined using collision-induced dissociation in ESI-tandem mass spectrometers. Experimental results for AAXAA, AVXLG, AAAXA, AGXGA, and AXPAA peptides are presented, where X represents Pro, Aze, Pip, or NMeA. Aze- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…1b, agrees well with the sequence XVPGVGVPGVGX, comprising an acetylated propargyl glycine at the N-terminus and an amidated propargyl glycine at the C-terminus. 70 The sodium ion affinities of proline (196 kJ mol −1 ), 68 valine (173 kJ mol −1 ) 68 and glycine (161 kJ mol −1 ) 68 follow the same order as the corresponding proton affinities (921, 911 and 887 kJ mol −1 , respectively 71 ). According to established peptide ion fragmentation mechanisms, [67][68][69] these fragments are generated by rearrangement fragmentations at the C(vO)-NH bonds which break the peptide into two segments, one containing the N-terminus and the other the C-terminus.…”
Section: Resultsmentioning
confidence: 92%
“…1b, agrees well with the sequence XVPGVGVPGVGX, comprising an acetylated propargyl glycine at the N-terminus and an amidated propargyl glycine at the C-terminus. 70 The sodium ion affinities of proline (196 kJ mol −1 ), 68 valine (173 kJ mol −1 ) 68 and glycine (161 kJ mol −1 ) 68 follow the same order as the corresponding proton affinities (921, 911 and 887 kJ mol −1 , respectively 71 ). According to established peptide ion fragmentation mechanisms, [67][68][69] these fragments are generated by rearrangement fragmentations at the C(vO)-NH bonds which break the peptide into two segments, one containing the N-terminus and the other the C-terminus.…”
Section: Resultsmentioning
confidence: 92%
“…In 2012, Hughey and two undergraduate students published an Analytical Chemistry paper that investigated the role of polar protic and aprotic solvents on negative-ion ESI. 52 Another group used LC-MS-MS with isobaric tags to measure metabolic changes in diabetic mice, 53 and a third group developed data acquisition and processing methods to interpret MALDI data into quantitative measures of the phosphoproteome. Another strategy at PUIs is to engage in collaborative MS research.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…[12,13] Consequently, proline has been part of many peptide fragmentation model studies. Proline-containing peptides have been shown to have a higher propensity for forming cis peptide bonds at the Pro residue as its barrier to trans/cis isomerization of the N-terminally adjacent peptide bond is ~55 kJ/mol compared to the average ~80 kJ/mol for the other 19 protein amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…[13,1720] In analysis of precursor peptides containing proline, Masson et al, using both spectroscopy and ion mobility, confirmed that GPGG was comprised of a larger kinetically trapped trans -Pro population and a smaller cis -Pro population that was found to be more thermodynamically stable in the gas-phase. [21]…”
Section: Introductionmentioning
confidence: 99%